Guanosine triphosphate acts as a cofactor to promote assembly of initial P-element transposase-DNA synaptic complexes. - Tang, M.; Cecconi, C.; Kim, H.; Bustamante, C.; Rio, D.C. (Genes & Development, 2005)
P transposable elements in Drosophila are members of a larger class of mobile elements that move using a cut-and-paste mechanism. P-element transposase uses guanosine triphosphate (GTP) as a cofactor for transposition. Here, we use atomic force microscopy (AFM) to visualize protein-DNA complexes formed during the initial stages of P-element transposition. These studies reveal that GTP acts to promote assembly of the first detectable noncovalent precleavage synaptic complex. This initial complex then randomly and independently cleaves each P-element end. These data show that GTP acts to promote protein-DNA assembly, and may explain why P-element excision often leads to unidirectional deletions.